Assessment of macular microvasculature features before and after vitrectomy in the idiopathic macular epiretinal membrane using a grading system: An optical coherence tomography angiography study. Issue 7 (10th January 2021) - Mao, Jianbo; Xu, Zhaokai; Lao, Jimeng; Chen, Yiqi; Xu, Xiaoqiong; Wu, Sulan; Zheng, Zicheng; Liu, Bowen; Shen, Lijun
Abstract: Purpose: To evaluate pre‐ and postoperative microvasculature features in eyes with different idiopathic macular epiretinal membrane (iERM) classifications using optical coherence tomography angiography (OCTA). Methods: In this retrospective study, 100 eyes with iERM were enrolled; 62 eyes underwent pars plana vitrectomy (PPV). All iERM eyes were evaluated and graded using optical coherence tomography (OCT). According to the thickness of the fovea relative to the surrounding macula from OCT radial line scans, we classified iERM into three grades. Optical coherence tomography angiography (OCTA) was used to measure the foveal avascular zone (FAZ)‐related parameters and the superficial and deep capillary plexus layers using 3 × 3 mm scans. Measurements were taken at baseline and 3 months postoperatively. Best corrected visual acuity (BCVA), vessel density (VD), FAZ area, FAZ perimeter (PERIM), acircularity index (AI), and foveal vessel density (FD) were evaluated. Results: Idiopathic macular epiretinal membrane (iERM) eyes with a higher grade had a lower FAZ area and perimeter (p < 0.0001), higher foveal vessel density (FVD) both in the superficial capillary plexus (SCP) (p < 0.0001) and in the deep capillary plexus (DCP) (p < 0.05), and a lower parafoveal vessel density (PRVD) in the DCP (p < 0.0001). The macular vessel density ratio (MVR = FVD/PRVD) increased with an increase in grade both in the SCP and in the DCP (p < 0.0001). For grade 1 iERM eyes, only PRVD in the DCP significantly changed before versus after the operation (p < 0.05). For grade 2 iERM eyes, the FAZ area and perimeter became larger after the operation (p < 0.05). The MVR of grade 2 iERM eyes decreased postoperatively both in the SCP (p < 0.05) and in the DCP (p < 0.001). For grade 1 and grade 2 iERM eyes, preoperative LogMAR BCVA was negatively correlated with the FAZ area (p < 0.01) and perimeter (p < 0.01), and was positively correlated with the MVR in the SCP (p < 0.05). Postoperative LogMAR BCVA was positively correlated with the FVD in the DCP (p < 0.05). Conclusions: Idiopathic macular epiretinal membrane (iERM) eyes of different grades have significant differences in microvasculature features. According to OCTA, eyes with higher grades have more serious microvascular changes. Grading plays a part in predicting postoperative microvascular characteristics, and grade 1 iERM eyes have a better visual outcome compared with grade 2 iERM eyes.